2021
DOI: 10.2147/jbm.s308861
|View full text |Cite
|
Sign up to set email alerts
|

Murine Leukemia-Derived Extracellular Vesicles Elicit Antitumor Immune Response

Abstract: Background: Extracellular vesicles (EVs) are heterogeneous lipid bilayer particles secreted by cells. EVs contain proteins, RNA, DNA and other cargo that can have immunomodulatory effects. Cancer-derived EVs have been described as having immunomodulating effects in vivo with immunosuppressive and pro-tumor growth capabilities. However, cancerderived EVs have also been harnessed and utilized for anti-cancer potential. Methods: To assess the immunomodulatory effect of EVs produced by acute myeloid leukemia (AML)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Reduced tumor growth and extended survival [ 33 ] Exosomes (TEXs) - Modification of gene expression of CD8 + , CD4 + and CD4 + CD39 + T cells. Significant CD8 + immune responses [ 34 , 35 ] CHOL/L-α-phosphatidylcholine (PC)-based liposomal formulation Lymphoma OVA/adjuvants (poly(I:C) and CpG ODN) (cancer vaccine) Synergistic effect of the adjuvants with the carrier. Immunization for 8 months with deceleration in tumor progression [ 20 ] C3-targeted liposomes (DPPC/1,2-distearoyl-sn-glycero-3-phosphocholine (DSPC)/DSPE-PEG2000) OVA antigen (cancer vaccine) Antigens delivered and internalized in APCs.…”
Section: Drug Delivery Approaches For Immunotherapy In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced tumor growth and extended survival [ 33 ] Exosomes (TEXs) - Modification of gene expression of CD8 + , CD4 + and CD4 + CD39 + T cells. Significant CD8 + immune responses [ 34 , 35 ] CHOL/L-α-phosphatidylcholine (PC)-based liposomal formulation Lymphoma OVA/adjuvants (poly(I:C) and CpG ODN) (cancer vaccine) Synergistic effect of the adjuvants with the carrier. Immunization for 8 months with deceleration in tumor progression [ 20 ] C3-targeted liposomes (DPPC/1,2-distearoyl-sn-glycero-3-phosphocholine (DSPC)/DSPE-PEG2000) OVA antigen (cancer vaccine) Antigens delivered and internalized in APCs.…”
Section: Drug Delivery Approaches For Immunotherapy In Cancermentioning
confidence: 99%
“…In this regard, Pando et al have recently reported the modification of gene expression of CD8 + , CD4 + , and CD4 + CD39 + T cells by using AML-derived extracellular vesicles. The authors reported in vitro and in vivo the impact of these TEXs on the induction of significant CD8 + immune responses [ 34 , 35 ].…”
Section: Drug Delivery Approaches For Immunotherapy In Cancermentioning
confidence: 99%